PERAN SUSTAINABILITY REPORTING TERHADAP PENINGKATAN KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR - Christina Verawati Situmorang; Arthur Simanjuntak (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
Sustainability reporting and business performance are important elements that have been studied over the last ten decades. The aim of this research is to reveal whether there is an impact of sustainability reporting on improving the performance of manufacturing companies listed on the Indonesia Stock Exchange. This is quantitative research where quantitative data is collected through secondary sources. The current research population includes manufacturing companies on the Indonesia Stock Exchange for the year ending 2023. The population in this research is 165 manufacturing companies consisting of the Basic Industry and Chemical Sectors; Miscellaneous Industrial Sector and Consumer Goods Sector. The sample size for this study was 98 manufacturing companies. This research tests the hypothesis and its variables using Partial Least Squares (PLS) software for data analysis. The results of the current research show that sustainability reporting has a significant positive impact on company financial performance (ROA). On the other hand, sustainability reporting has a significant positive impact on the company's financial performance (ROE). This research also has practical implications, where we believe that directors must strive to balance sustainability reporting with the expected increase in company performance. In addition, empirical evidence regarding the implications of this research shows that although most manufacturing companies on the Indonesia Stock Exchange that want to improve their performance have recently focused on sustainability reporting, they should focus more on this report and see the benefits of this report for the business world in promoting business. This also adds value to this research, because this research can be considered as one of the research conducted on manufacturing companies on the Indonesia Stock Exchange in 2023. This introduces new insights into the body of knowledge about the role of sustainability reporting in improving company performance. Likewise, conducting research in the fields of management, business and finance will provide new insights into sustainability reporting, which in the end can help companies improve the company's financial performance